Seismological data versus rheological modelling: Comparisons across the Aegean Region for improving the seismic hazard assessment. (April 2021) - Maggini, M.; Caputo, R.
Abstract: Compared analyses of the seismicity cutoff depth and the corresponding BDT (brittle-ductile transition) depth obtained from rheological modelling have been performed for numerous test sites all over the Aegean Region. The major goal of this research is to determine whether the rheological transition could be effectively correlated to the seismological one, so that both information can independently contribute in determining the seismogenic layer thickness and hence in constraining the maximum width of active faults affecting a region. As concerns the seismological data, only relocated events have been considered for the purpose of this paper, included either in seismic sequences associated with a mainshock, or in datasets of background seismicity. In the same areas, we carried out rheological modelling for reconstructing the local strength envelope, focusing our attention on the BDT depth. The systematic comparison at the investigated sites indicates that 90% of the relocated seismicity always occurs within the corresponding rheological transition. Moreover, for the datasets also providing magnitudes, 99% of the total seismic scalar moment is always released above the BDT depth. Such results are verified for different tectonic regimes and geological settings, both extensional, transcurrent and compressional. The achieved results confirm that the BDT depth based on accurate strength envelopes could be considered a reliable indicator for the thickness of the seismogenic layer, thus contributing to constrain the maximum widths for active faults affecting those regions. Based on these constraints, we also applied some empirical relationships to estimate the possible maximum magnitude for seismogenic sources in correspondence of the tested sites, thus potentially improving our seismic hazard assessment analyses for these areas.